South-North Partnership in Agricultural Education - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
South-North partnership in strengthening higher education in agriculture', edited by W van den Bor, J C M Shute, and G A B Moore, 1989. 339 pages hardback, ISBN 90 7701001 5, price Dfl.80.00, US$46.00.